Pengaruh Internal Marketing dan Kualitas Pelayanan BPJS Kesehatan Terhadap Kinerja Melalui Kepuasan Dokter di RSUD Ulin Banjarmasin) - Rismayanti Rismayanti; Martha Irene Kartasurya; Nico L. Kana (Jurnal Manajemen Kesehatan Indonesia, 2016)
Internal marketing and service quality BPJS are things that influence the level of satisfaction of doctors that becomes the deciding factor of doctor performance. The aim of this study is to find the influence of internal marketing and service quality performance of BPJS Kesehatan with doctor performance through doctor satisfaction at RSUD Ulin Banjarmasin. This type of research is analytic with cross sectional design. The research method was developed using a questionnaire based on the literature. The number of respondents who came from the science of internal medicine, pediatric, obstetrical and gynaecology, and surgery and met the inclusion criteria as many as 52 people were surveyed. Data was analyzed using Pearson correlation and multiple linear regression. The results showed correlation between internal marketing to the satisfaction of doctors (r = 0.584, p = 0.000), between service quality BPJS and satisfaction of doctors (r = 0.499, p = 0.001), between the satisfaction of doctors and the performance of doctors (r = 0.583, p = 0.0001). Results of research by multiple linear regression analysis showed that the internal marketing and service quality BPJS have contributed influence on physician satisfaction of 44.6% while 55.4% described other factors. Physician satisfaction have contributed influence on physician performance by 32.7% while 67.3% described other variables outside the model. It was concluded that internal marketing and service quality effect on doctors satisfaction which in turn affect the performance of doctors. Suggested to BPJS Health to improve the financing system INA-CBG’s and disseminate laws and regulations better.